Psychologiczne bariery udzielania pomocy medycznej dziecku = Psychological barriers in delivering first help for child - Rafał Czyż; Marta Sarnowska; Radosław Rutkowski; Kamila Kotowicz (Kazimierz Wielki University, 2016)
Czyż Rafał, Sarnowska Marta, Rutkowski Radosław, Kotowicz Kamila. Psychologiczne bariery udzielania pomocy medycznej dziecku = Psychological barriers in delivering first help for child. Journal of Education, Health and Sport. 2016;6(5):403-411. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.53173 http://ojs.ukw.edu.pl/index.php/johs/article/view/3534     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016.   Psychologiczne bariery udzielania pomocy medycznej dziecku Psychological barriers in delivering first help for child   Rafał Czyż1 (rafalczyz1990@o2.pl), Marta Sarnowska2, Radosław Rutkowski3, Kamila Kotowicz4 1) Katedra Medycyny Ratunkowej Uniwersytetu Medycznego we Wrocławiu 2) Katedra Zdrowia Publicznego Uniwersytetu Medycznego we Wrocławiu 3) Katedra Biofizyki. Samodzielna Pracownia Biofizyki Układu Nerwowego Uniwersytetu Medycznego we Wrocławiu 4) Katedra i Klinika Psychiatrii Uniwersytetu Medycznego we Wrocławiu   Abstrakt Udzielanie pierwszej pomocy niejednokrotnie wymaga od potencjalnego ratownika przełamywania wielu wewnętrznych barier. Gdy dochodzi do zagrożenia życia lub zdrowia dziecka czynniki te w szczególności nasilają się i w istotnym stopniu determinują dalsze działania osoby niosącej pomoc na miejscu zdarzenia.   Celem pracy była próba identyfikacji czynników psychologicznych, mogących wpływać na chęć udzielania pomocy dziecku w stanie nagłym.   W badaniu wzięło udział 114 studentów w wieku 22,1±1,6 lat. Użyto autorskiej ankiety, składającej się z pytań, próbujących określić owe czynniki oraz testu wiedzy z zakresu pierwszej pomocy.   Większość(65%) ankietowanych deklaruje ukończenie szkolenia z zakresu pierwszej pomocy osobie dorosłej, natomiast dziecka - zaledwie 42% studentów. Zaskakującym jest fakt, iż w ponad 80% szkoleń nie podjęto tematu dotyczącego pediatrycznej wersji AED. Wysoki odsetek studentów(60%) deklaruje podjęcie pomocy dziecku w sytuacji zagrożenia jego życia. Pozostała część ankietowanych, jako największą barierę w udzielaniu pomocy dziecku, określa obawę przed pogłębieniem istniejącego już urazu(54%). Dodatkowo częstymi powodami odstąpienia od pomocy są: brak wiedzy i umiejętności udzielania pomocy(30%), strach związany z zaistniałą sytuacją(21%) oraz obawa przed pociągnięciem do odpowiedzialności prawnej za wyrządzenie krzywdy(20%). W porównaniu płci, kobiety uzyskały wyższy średni wynik testu wiedzy niż mężczyźni (5,10±1,6vs.4,86±1,6), aczkolwiek zdecydowanie częściej w ankiecie wskazują jej brak jako czynnik ograniczający niesienie pomocy.   Występowanie wielu czynników ograniczających studentów w udzielaniu pomocy dzieciom niesie za sobą konieczność organizowania systematycznych szkoleń z zakresu pierwszej pomocy.   Słowa kluczowe: pierwsza pomoc, bariery psychologiczne.     Psychological barriers in delivering first help for child   Delivering first aid many times requires from potential rescuer breaking many inside barriers. When occurs emergency situation where the child's  health or life is endangered all of this factors intensify and in significant degree are determining further actions of the person delivering help on the spot.   Aim of this study was an attempt of identification of psychological factors, being able to influence on willingness to deliver medical help for child in emergency state.   In examination took part 114 students aged 22.1±1.6 years. Author's questionnaire form was used. It consisted of questions which were trying to determine those psychological factors and first aid medical knowledge test.   Majority (65%) of participants declare the fact of completion of adult first aid course, however of child first aid course - only 42% of students. Suprising is a fact, that in over 80% of trainings a subject of the paediatric AED version wasn't raised. High percentage of students (60%) declaring willingness of taking the help to the child in emergency state. The rest part of respondents, as the biggest barrier in help for child, is defining anxiety of deepening the already existing injury (54%). Additionally frequent reasons of giving up the help were: lack of knowledge and skills in delivering medical help (30%), fear associated with the existing situation (21%) and anxiety of drawing to the legal liability for harming (20%). In comparing the sex, women obtained higher average medical knowledge test results than men (5.10±1.6 vs 4.86±1.6), although definitely more often in questionnaire form show its lack as a limiting factor in delivering help.   Occurrence of many factors which limiting students in delivering medical help for children bringing the need to organize systematic first aid courses.     Key words: first help, psychological barriers.